Development of Rehabilitation Services under the Healthy China Strategy - Lidian CHEN (康复学报)
Driven by the healthy China strategy, the medical and health services in China have gradually risen from focusing on the treatment of a single disease to paying more attention to the improvement of overall health. Rehabilitation, as a service to maintain and improve functions, is an important part of the healthy China project. This article explored the changes of rehabilitation service objects, the expansion of rehabilitation service scopes, the characteristics of multidisciplinary integration of rehabilitation medicine, the role of traditional Chinese medicine (TCM) in disease rehabilitation, the main ways of developing rehabilitation services in China and the necessity of carrying out evaluation of rehabilitation outcome under the current situation, providing a new perspective for promoting the development of rehabilitation services in our country.